The Viewpoint of the Sharia System on Digital Marketing during the Covid 19 Pandemic - M Dana Prihadi; Ratih Hurriyati; Puspo Dewi Dirgantari (Budapest International Research and Critics University, 2022)
Shopping online as a new lifestyle is common in the Covid-19 pandemic. The emergence of various e-commerce platforms in Indonesian society has become a new alternative that facilitates the current pattern of people's shopping behavior. Many companies are experimenting with decentralized decision making and software to make new digital work cultures more effective and productive as working in a physical office. The existence of this pandemic can encourage consumers who do not like online shopping to finally switch to online shopping. With a phenomenon like this, the research was conducted with the aim of obtaining findings regarding the description of the application of digital marketing during the COVID-19 period seen through sharia viewpoint. This type of research uses descriptive analysis method, namely by analyzing independent variables without making comparisons and looking for correlations with other variables. From the research that has been done, it is found that every company or producer should pay attention to the condition of the products being marketed, especially in terms of Islamic law (halal and haram) and for online buying and selling transactions there is no element of usury (interest) and maisir (gambling). With the research that has been done, it is expected to increase the profit of the company or producer.